(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Respect for freedom of worship and recognition of religious diversity based on the guidelines proposed by human rights is a recurring challenge in the Brazilian context. Respect for diversity is affirmed by overcoming prejudices and discrimination, especially when the system of values ​​and truths is not placed as a global parameter. Religious freedom, for example, should not be confused with the freedom of religious promotion in public agency spaces and the interference of religion and its truth systems in civil acts of public interest. The hermeneutical path, presented here, seeks to clarify issues related to religion at its interfaces with laicity and diversity. The objective of this approach, therefore, is to broaden the conceptual and comprehensive horizon, through a documentary and bibliographic analysis, on the incidence of religion in the current public sphere, based on its deployment with fundamentalisms, diversity, equity and social justice.